"La vita degli affari“ of Massimo Bontempelli. The literary text in the editorial context of «a technical magazine of production» (Prassi Ecdotiche della Modernità Letteraria, 2021)
The essay analyses the relationship between Massimo Bontempelli’s La vita degli affari and «Le I.I.I.», a review that updated its readers on industry-related technical developments, which first published the novel in 1920. The novel, based on an ambiguous oscillation between contraries, requires strong self-irony to «Le I.I.I.» readers, as it distorts the myths and mottos of the review. On the contrary, the review tries to moderate the strongest parodical elements of the text by encompassing the novel into its all-encompassing project.
Keywords: Bontempelli; La vita operosa; La vita degli affari; First edition; Le I.I.I.; Industrie Italiane Illustrate